Implementation and Student Response to Phonics Songs for Beginning Readers: A Case Study at SD Bangkala III Makassar - Amal, Budi; Munandar, Aris; H, Nurhikmah; Kusuma, Sholihatunnisa Dwi (PPSDP International Journal of Education, 2025)
This study aims to analyze the implementation and student response to the Phonics Reading Songs media as a preliminary trial at SD Bangkala III Makassar. This qualitative case study focuses on 15 progressive songs that emphasize phonemic awareness, ranging from letter recognition to syllable blending. Data were collected through participatory observation and in-depth interviews with classroom teachers and students. The results showed that the Phonic Song media proved to be practical and easy for teachers to implement. Affectively, first-grade students at SD Bangkala III Makassar, including those who had difficulty reading, showed positive responses, increased enthusiasm, and active involvement in learning. Cognitively, Phonics Songs function effectively as an auditory mnemonic that strengthens phonological memory and facilitates the blending of phonemes into syllables. These findings are supported by preliminary evidence of efficacy in a preschool context, indicating the suitability of this medium for early reading intervention. This case study concludes that the integration of rhythm and phonics is an effective approach to overcoming early reading difficulties. Further quantitative research is needed to measure the broader impact.